Analisis Pengaruh Indikator Ekonomi Makro terhadap Perkembangan PT. Bank Cimb Niaga Tbk - Pramono Margono (UniSadhuGuna Business School, 2020)
This study aims to discuss the influence of macroeconomic variables on the performance of PT Bank CIMB Niaga Tbk. The study was conducted based on financial ratios of PT Bank CIMB Niaga Tbk. During the period September 2006 until December 2010. The study used multiple linear regression method to determine the dependent variable is the ratio of CAMELS (CAR, PPAP, ROA, ROE, NIM, BOPO and LDR) and independent variables are macroeconomic variables (inflation rate, Exchange Rate Euro Against Dollar, Interest Rate SBI and the Money Supply (M2)). The results using SPSS version 19.0 including tests of normality, multicollinearity test, test heteroscedasticity, autocorrelation test and multiple linear regression test showed that the macroeconomic variables that most influence on the performance of PT Bank CIMB Niaga Tbk is the exchange rate of rupiah against the U.S. dollar negatively (not direction) of the ROE of 97.28%. And in PT Bank CIMB Niaga Tbk, which have increased after the merger is the ratio of PPAP, ROA, ROE and NIM. While the ratio of CAR, and LDR BOPO PT. CIMB Niaga Tbk has decreased.